Sustained High Levels of Both Total and High Molecular Weight Adiponectin in Plasma during the Convalescent Phase of Haemorrhagic Fever with Renal Syndrome Are Associated with Disease Severity - Kang Tang; Chunmei Zhang; Yusi Zhang; Yun Zhang; Ran Zhuang; Boquan Jin; Ying Ma (Journal of Immunology Research)
Haemorrhagic fever with renal syndrome (HFRS) is characterised by an uncontrolled immune response that causes vascular leakage. Adiponectin (APN) is an adipocytokine involved in prorevascularisation and immunomodulation. To investigate the possible effects of APN in the pathogenesis of HFRS, total and high molecular weight (HMW) APN levels in the plasma of patients with HFRS were quantified using enzyme-linked immunosorbent assay (ELISA). Compared with those in healthy controls, the plasma total and HMW APN levels in patients were elevated to different degrees from the fever onset and remained high at the convalescent phase. Consistent with these results, western blot analysis additionally showed that low molecular weight (LMW), middle molecular weight (MMW), and HMW APN levels were all elevated and contributed to the elevation of the total APN level. Importantly, sustained high levels of total and HMW APN at the convalescent phase were significantly higher in patients with critical disease than those in patients with mild or moderate disease. Moreover, total and HMW APN levels negatively correlated with white blood cell count and positively correlated with platelet count and serum albumin level. These results may provide insights into understanding the roles of total and HMW APN in the pathogenesis of HFRS.